Technology-based Business Incubator Model as Efforts to Improve the Learning Process - Hurriyati, Ratih; A, Ana; Hassan, R.; C.S, Lai (International Journal of Engineering and Technology, 2018)
This paper tries to identify technology-based business incubator models as an effort to improve the right learning process. The method used is an experimental method, where in the early stages the criteria for learning technology-based business incubator learning criteria are developed by integrating pedagogical aspects and technological aspects that will be used as experiments through need assessment, then proceed with making a model design. Model design based on the teaching model that will be applied. In the next stage, the implementation of the trial was carried out by using the teaching model and the entrepreneurship courses that were set, and then conducted a trial on the technology-based business incubator learning system with the same teaching model and courses and the same students. The results of this study produce a learning system that is able to create individuation, acceleration, enrichment, expansion, effectiveness and productivity of learning which in turn will improve the quality of education as an overall human-resource development infrastructure.Â